Are dietary interventions effective in the treatment of multiple sclerosis?. Issue 2 (February 2015) - Wirtz, Mark; Tring, Vi Song; Algert, Lesley; Elliot, Jonathan
Abstract : Evidence‐Based Answer : Apparently no. Polyunsaturated fatty acid (PUFA) and vitamin D supplementation (along with interferon treatment) have not been shown to improve outcomes in patients with multiple sclerosis (MS) (SOR: B, systematic review of low‐quality RCTs and small RCT).